Nezajem poverenych. Pristup ceskych politiku a politicek, uredniku a urednic k otazkam genderove rovnosti v obdobi pred vstupem CR do EU - Krizkova, Alena (Gender, Equal Opportunities, Research, 2006)
The author argues that the attitudes of disinterest and ignorance of the Czech governmental officials and politicians towards gender equality during the period of EU Eastern enlargement was one of the most important factors that shaped the character of the promotion of women and gender equality. The text is based on analyses of semi-structured interviews with politicians and officials from the Czech government, and representatives of the European Commission carried out between 2003 and 2005. The strategy of the Czech government was to mechanically adopt everything that constitutes a precondition for the Czech Republic's accession to the EU. It is possible to observe two main, closely related factors in the attitude of the state towards these issues: firstly the conviction that there is no need or even demand on the part of society for any substantial legislative measures addressing gender equality or for the development of relevant infrastructure, as equality is already essentially established in the Constitution of the Czech Republic. The introduction of EU equality directives into the Czech legislation was perceived by Czech politicians a simple, technical task, required as one of the preconditions for EU accession. The second factor was the emphasis on the negative experiences with egalitarian policies under the communist regime. These two factors resulted on the one hand in a lack of sufficient trust on the part of the public and on the other hand in a lack of steps to implement this legislation and put the new institutions into practice.
Keywords: Gender equality legislation; EU eastern enlargement; Attitudes of Officials